Teachers' perception of the english language textbook for sixth grade in the Kingdom of Saudi Arabia - Sharbib, Saleha Ibrahim (Institute of Education, International Islamic University Malaysia, 2012)
The government of Saudi Arabia has invested substantially in the further development of English language education. One important step has been the introduction of English textbooks for the sixth grade. The successful introduction of a new English textbook for public schools has been based on the assumption that it would encourage and support learning in the form of English communication activities. Whether or not this assumption is being translated into reality, however, depends partly on the English teachers' perceptions of the textbooks. This study aimed to evaluate the English textbooks taught at sixth grade primary stage from an educational viewpoint. It was quantitative in nature and employed a descriptive research design utilising a sample size of 182 English teachers. The results of this study indicate that the majority of respondents had positive perceptions toward most of the domains addressed in this study except for the issues related to the general aspects of the textbook and teacher's book. However, the demographic variables played a key role in determining their perceptions towards the English textbooks. It is found that male teachers were more likely to perceive the English textbook more positively than female teachers at Saudi public schools. In terms of training courses, the teachers who had had more than five training courses in the field of curriculum and instructitm were more likely to have different views about the English textbooks than those who had received less than five training courses.